2020
DOI: 10.1002/jcla.23191
|View full text |Cite
|
Sign up to set email alerts
|

Role of hematological parameters in the diagnosis of influenza virus infection in patients with respiratory tract infection symptoms

Abstract: Background: The differential diagnoses of patients hospitalized for respiratory infections due to influenza virus vs other pathogens are challenging. Our study investigated whether hematological parameters such as neutrophil (N), lymphocyte (L), platelet (PLT), and neutrophil-to-lymphocyte ratio (NLR) contributed in diagnosing influenza virus infections and in discriminating other respiratory infections. Methods: We retrospectively analyzed the laboratory characteristics of 307 patients with respiratory infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 23 publications
10
46
1
4
Order By: Relevance
“…This is consistent with previous studies showing that no single hematologic marker carried sufficient weight to confirm or refute specific respiratory virus 24,25 . In contrast, Han et al 14 reported that hematologic markers provided an adjunct diagnostic approach in the differential diagnosis of respiratory infections due to influenza virus and other respiratory viruses, but their study did not include patients infected with SARS‐CoV‐2. Thus, the diagnostic value of hematologic markers for different respiratory virus infection deserves more studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous studies showing that no single hematologic marker carried sufficient weight to confirm or refute specific respiratory virus 24,25 . In contrast, Han et al 14 reported that hematologic markers provided an adjunct diagnostic approach in the differential diagnosis of respiratory infections due to influenza virus and other respiratory viruses, but their study did not include patients infected with SARS‐CoV‐2. Thus, the diagnostic value of hematologic markers for different respiratory virus infection deserves more studies.…”
Section: Discussionsupporting
confidence: 89%
“…NLR has been demonstrated as an informative biomarker of diagnosis and disease severity in community‐acquired pneumonia and bacteremia 10,11 . MLR and PLR have also been recognized as a surrogate biological marker for the diagnosis of influenza virus infection in patients with respiratory tract infection 12‐14 . However, few studies have focused on the diagnostic value of hematologic markers for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NLR has some predictive value in the diagnosis of disease and severity in patients with influenza virus and other inflammation-related diseases. [13][14][15][16] Our results showed that the NLR in the severe group was significantly higher than that in the nonsevere group. The area under the ROC curve of the NLR predicting the severity of COVID-19 was the largest.…”
Section: In Terms Of Laboratory Tests the Main Characteristics Of Comentioning
confidence: 46%
“…In cases of other viral and bacterial pneumonia, NLR was more sensitive than individual levels of neutrophils and lymphocytes [40]. Similarly, PLR correlated well with mortality and disease severity in bacterial pneumonia [12,41].…”
Section: Discussionmentioning
confidence: 82%